Penentuan Rute Distribusi Produk Otomotif dengan Metode Saving Matrix dan Traveler Sales Problem - Permana, Ferdy Dwi; Tarigan, Zeplin Jiwa Husada (Institut Teknologi Adhi Tama Surabaya, 2020)
PT. Star Spart Indonesia in Sidoarjo, East Java is an automotive and spare part company which sells various national and international quality automotive products such as baterries, oil, tyres, and other spare parts. In promoting the products, this company is facing many competitors, so it has to collaborate with other retail shops and main dealers to win the competition. Therefore, the company is planning a proper marketing strategy to market the products in order to strive the organizational goals (to survive, to grow, and to multiply). This research is using Saving Matrix method to schedule limitied transportation vehicles to deliver goods from one facility to various customers. Another method is using the Farthest Insert, Nearest Insert and Nearest Neighbour method. Using the Saving Matrix method, the company can spend Rp. 45,802,836 for transportion costs using company's vehicles. If the company rents the vehicles to other outsourcing company, the transportation costs will be Rp. 49,000,000. There is a saving of Rp. 3,197,164 if the company uses own vehicles. From changing the route, there will be another cost saving from fuel as much as Rp. 409,115. Keywords: Saving Matrix, Farthest Insert, Nearest Insert, Nearest neighbour, Distribution